Mediating effect of social constraints in the association between stigma and depressive symptoms in Chinese breast cancer patients - ChunYing Cui; Lie Wang (BMC Psychiatry)
Abstract Purpose The present study aimed to investigate the effect of stigma on depressive symptoms and explore the mediating role of social constraints between stigma and depressive symptoms in Chinese breast cancer (BC) patients. Methods A cross-sectional design was conducted in China from December 2020 to July 2021. Out of 256 participants, 222 BC patients completed the questionnaires composed of demographic and clinical information, Patient Health Questionnaire-9 (PHQ-9), Social Impact Scale (SIS), and 15-item Social Constraints Scale (SCS-15). The hierarchical regression analysis was adopted to explore the associations of stigma and social constraints with depressive symptoms and the mediating role of social constraints. Results Approximately 20% of participants reported having depressive symptoms in Chinese BC patients. The indirect effect of stigma on depressive symptoms through social constraints was significant (a*b = 0.24, 95%CI = 0.15–0.33). When the mediator was controlled for, the direct impact of stigma on depressive symptoms was also significant (c’=0.16, p < 0.01). Conclusion The current study suggested that stigma may contribute to developing depressive symptoms by increasing social constraints in Chinese BC patients. Interventions based on reducing stigma and social constraints should be conducted to improve mental health in BC patients.